26. THE SITUATION OF INCIDENCE AND MORTALITY RATES OF INFECTIOUS DISEASES IN SON LA PROVINCE PERIOD 2016-2023 (Vietnam Journal of Community Medicine, 2025)
2016-2023.Method: Cross-sectional descriptive study combined with secondary data analysis.Results: In the group of respiratory infectious diseases, influenza has the highest incidence rate per 100,000 people, with an average of 1209.7 cases/100,000 people, followed by chickenpox (66.9 cases/100,000 people), mumps (47.1 cases/100,000 people), and measles (19.5 cases/100,000 people). Common infectious diseases in the digestive system group include diarrhea, dysentery (bacillary dysentery), amoebic dysentery, and hand-foot-mouth disease, with incidence rates per 100,000 people of 614.4, 19.5, 13.5, and 11.7, respectively. The group of blood-borne, skin, and mucous membrane infectious diseases had lower case numbers. There were 65 deaths due to other viral encephalitis, neonatal tetanus (27 cases, mortality/incidence ratio from 0.4-1), and rabies (24 cases, mortality/incidence ratio of 1).Conclusion: Respiratory and digestive infectious diseases are the two most common groups, with typical diseases such as influenza, diarrhea, chickenpox, mumps, etc. Some diseases causing death include other viral encephalitis, rabies, neonatal tetanus, Japanese encephalitis, and diarrhea. Among them, rabies and neonatal tetanus have a high mortality/incidence ratio.
Keywords: Infectious diseases; incidence rate; mortality rate; Son La province.